Renal differentiation from adult spermatogonial stem cells. (November 2013) - Heer, Rakesh; Hepburn, Anastasia C.; Williamson, Stuart C.; Kennedy, Amy; El-Sherif, Amira; Soomro, Naeem A.; Brown, Colin D.A.; Robson, Craig N.
Abstract There is considerable interest in the use of multi-potent stem cells in kidney tissue regeneration. We studied if spermatogonial stem cells have the ability to undergo kidney differentiation. Spermatogonial stem cell differentiation was induced using in vitro and ex vivo co-culture techniques. Conditioned media from human kidney fibroblasts induced the expression of epithelial and endothelial lineages in spermatogonial stem cells, consistent with nephrogenesis. Furthermore, we showed that these cells up-regulated renal tubular-specific markers alkaline phosphatase, mineralocorticoid receptor, renal epithelial sodium channel and sodium-glucose transporter-2 (p < 0.05). GFP-labeled spermatogonial stem cells were engrafted into metanephric kidney organ cultures harvested from E12.5 mouse embryos. After 5 days of organ culture, focal anti-GFP staining was detectable in all inoculated kidneys demonstrating integration of spermatogonial stem cells into the developing kidney (p < 0.01). Histological assessment showed early nephron-like architecture. In summary, we show that spermatogonial stem cells have the potential to generate renal tissue and lay the foundations for further investigations into a novel therapeutic approach for renal insufficiency.